PEMETAAN POLA SUHU PERMUKAAN TUBUH KUDA MENGGUNAKAN KAMERA TERMAL INFRAMERAH - Koekoeh Santoso; Rivangga Yuda Hendika; Mokhamad Fakhrul Ulum; Amrozi .; Ridi Arif; Agik Suprayogi; Kudang Boro Seminar (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2023)
Infrared thermal camera is an alternative and non-invasive method used to identify various physiological and pathological process related to body surface temperature changes. The aim of this research was to study the body surface temperature pattern based on the observed regios. Three horses were randomly selected as animal experiments. Thermal image data was collected at 17.00 – 19.00 WIB for five days. Images were retrieved from seven regios: head, thorax, abdomen, and four lower legs. The result of horse A’s surface temperature in five days on head, thorax, abdomen, front left leg, front right leg, rear left leg, and rear right leg regios were 33.42, 33.49, 33.56, 31.30, 31.48, 31. 33.14, 31.34 °C, respectively. The resulf of horse B’s surface tempereture were 33.55, 33.65, 33.64, 31.45, 31.35, 31.53, 31.48 °C, respectively. The resulf of horse C’s surface tempereture were 33.45, 33.55, 33.60, 31.37, 31.45, 31.34, 31.42 °C, respectively. The result showed that difference on horse A’s rear left leg (p<0.05) because of inflamation. Inflamation recovery process on horse A occured on the fifth day, indicated by a drop in temperature and a change in colors on thermal image. Color noises on some images were color difference between objects and poor color saturation. Color noises on thermal images did not affect the results of temperature interpretation.